THE APPLICABILITY OF TEACHING STYLES ACCORDING TO MUSKA MOSSTON BY PHYSICAL EDUCATION TEACHERS OS SCHOOLS OF RIO DE JANEIRO (Fiep Bulletin - online, 2013)
The physical education at school is a matter of intense debates as regards the practical application of all methodology theories that exists in the area. This research aims to analyze  the methodology processes that are developed in the physical education classes, identifying the teaching styles by Muska Mosston (1986) used by teachers  in the private schools. A descriptive and qualitative methodology was applied, and the sample consisted in 12 teachers, of both sexes, of elementary school. These professionals work in private schools located in Rio de Janeiro city, in Méier and nearby. In the results presented, the command style predominated with 50% in the classes of the teachers observed. The task style represented 34%. The oriented discovery and the inclusion styles, 8% each one. The command style has as its main characteristics the technicality, the traditional methodology trend, and the evaluation prioritizes the motor domain, and there is also a lower frequency of dialogue between the teacher and the student. The student active participation in the teaching-learning process has been valued now-a-days because this participation stimulates the formation of a citizen who is conscious, critical, creative and autonomous. This way, it is necessary to avoid the use of teaching methodologies as the styles command and task. Given these considerations, considering the teacher importance in the citizen formation according to the proposals of (PCN, 1997),   the research indicates the necessity of a reassessment of the theoretical references, resorting to others teaching methodologies, aimed the improvement in the preparation of physical education classes following the current trends in education.
Keywords: Teaching styles; Physical education at school; Teaching methodology.